2001
DOI: 10.1039/b009601f
|View full text |Cite
|
Sign up to set email alerts
|

Reaction and complex formation between OH radical and acetone

Abstract: Kinetics and mechanism of the reaction of OH with have been studied by discharge-Ñow CH 3 C(O)CH

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
88
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(111 citation statements)
references
References 19 publications
15
88
8
Order By: Relevance
“…Vasvári et al argued for OH abstraction from C-H bonds via a transition state ͑TS͒ in the plane of the carbon atoms, or addition to the central carbon atom normal to this plane, with weakly bound adducts at the entrances of both paths. 6 They commented that the high barrier they found for formation of a covalently bound adduct was inconsistent with their observations, and that a new unidentified mechanism might operate at low temperatures. Vandenberk et al presented a qualitatively different potential energy surface, with channels for addition, direct abstraction and abstraction via a hydrogenbonded intermediate.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Vasvári et al argued for OH abstraction from C-H bonds via a transition state ͑TS͒ in the plane of the carbon atoms, or addition to the central carbon atom normal to this plane, with weakly bound adducts at the entrances of both paths. 6 They commented that the high barrier they found for formation of a covalently bound adduct was inconsistent with their observations, and that a new unidentified mechanism might operate at low temperatures. Vandenberk et al presented a qualitatively different potential energy surface, with channels for addition, direct abstraction and abstraction via a hydrogenbonded intermediate.…”
Section: Introductionmentioning
confidence: 93%
“…All experiments were conducted at a total pressure of 735Ϯ10 torr with helium as the bath gas. High purity samples ͑Ͼ99.9%͒ of acetone and acetone-d 6 were obtained from Aldrich, Inc. and used as received, and GC/MS analyses indicated the absence of any reactive impurities that would impact the rate measurements. Analysis of the reactor gas stream showed that HONO generation did not produce detectable concentrations of potentially interfering NO, NO 2 or HCl (Ͻ1.2ϫ10 12 molecule cm Ϫ3 ).…”
Section: Experimental Approach and Data Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is in accordance with the known electrophilic behavior of the hydroxyl radical in its elementary reactions. k 1 is about five times smaller than the rate constant of OH with acetone given for one methyl group, i. e., (1/2) x k(OH + CH 3 C(O)CH 3 ) = 5.2 x 10 10 cm 3 mol -1 s -1 (T = 298 K) [6].…”
Section: Resultsmentioning
confidence: 84%